2020
DOI: 10.1371/journal.pone.0231148
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the effectiveness of WhatsApp for teaching doctors preparing for a licensing exam

Abstract: Conclusion WhatsApp can be an effective tool for health professional education, using a pre-defined curriculum coupled with organizational structure. This study reported both subjective and objective measures of effectiveness and demonstrated that the use of multiple e-learning resources can lead to improved learning outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Where this could be ascribed to the growing burden and hectic schedules of the healthcare workers, nonetheless, it signifies the need for methodical and structured management by the administration to take initiatives in educating healthcare workers. The effectiveness of imparting information via WhatsApp and other social media applications is consistent with some of the studies such as the survey done by Oyewole et al to determine the efficacy of WhatsApp to teach doctors for an exam, and a study conducted in Saudi Arabia in which social media was used by diabetics to communicate about the disease ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 79%
“…Where this could be ascribed to the growing burden and hectic schedules of the healthcare workers, nonetheless, it signifies the need for methodical and structured management by the administration to take initiatives in educating healthcare workers. The effectiveness of imparting information via WhatsApp and other social media applications is consistent with some of the studies such as the survey done by Oyewole et al to determine the efficacy of WhatsApp to teach doctors for an exam, and a study conducted in Saudi Arabia in which social media was used by diabetics to communicate about the disease ( 13 , 14 ).…”
Section: Discussionsupporting
confidence: 79%
“…Although social media can offer effective tools in the TB learning process, most of the respondents considered social media to be unhelpful. A previous study concluded that the curriculum must be pre‐defined and well‐structured to ensure the effectiveness of these tools for professional TB learning, 16 whilst the failure to meet these requirements could explain the negative responses in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Distance learning has been shown to have a positive influence on students’ learning outcomes such as learning satisfaction 15 . In this context, social media including WhatsApp and other applications such as Google class, Edmodo and Zoom can be valuable tools in conveying online learning 16 . Furthermore, it has been shown that a combination of the distance TB learning and conventional styles brought optimum student performance and satisfaction 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, students who were more heavily engaged in blog-based discussion of relevant learning material had higher grades than peers who had contributed less to the discussion [109]. Passing an examination was significantly associated with combining discussion on a WhatsApp group with the web-based question bank, and so were their higher grades [110]. Medical students who used Wikipedia had superior short-term knowledge acquisition compared with those who used a digital textbook, which suggested a potential role for Wikipedia in medical education [111].…”
Section: Professional Medical Educationmentioning
confidence: 95%